The relation between CEO equity incentives and the quality of accounting disclosures: New evidence - Wruck, Karen H.; Wu, YiLin (Journal of Corporate Finance, 2021)
This paper provides new evidence on the negative relation between CEO equity incentives and accounting disclosure quality. We analyze a comprehensive set of disclosure quality variables, including discretionary accruals quality, the quantity and quality of voluntary disclosures, fineness of reported financial statement information, and the narrative quality of regulatory filings, and use them to create information disclosure quality indices. We address the potential endogeneity of CEO equity incentives by conducting two-stage least squares/IV models and natural experiments created by situations in which there is an exogenous shock to the use or value of CEO stock options. Our results are robust to subsample analyses and to alternative measures of the incentives created by CEO options.